Acoustical shadow of a sphere immersed in water. I - FILIPCZYŃSKI, Leszek; KUJAWSKA, Tamara (Archives of Acoustics, 1989)
In this study the acoustical field behind a rigid sphere is determined for the incidence of a plane harmonic wave on it. This field was determined as the sum of acoustic pressures of the wave incident on the sphere and reflected from it. Formulae describing the reflected wave pressure given in different form by American, Japanese and Soviet acousticians, were compared and their identity demonstrated. It was shown, that these formulae, though valid for fixed spheres, can in practical hydroacoustic cases be also used for movable spheres. On this basis directional characteristics of the shadow behind the sphere were determined for the values of ka = 100π, 40π, 20π and 8π, which are essential for hydroacoustic problems and for ultrasonic medical diagnostics. These characteristics were determined for distances falling between 10 a and 100 a, where a denotes the radius of the sphere. Moreover, the shape of directional characteristics was interpreted and the ranges of the shadow were determined for different values of ka.